Optimization of the loading patterns of silica gels for o‐xylene recovery by vacuum swing adsorption. (5th October 2020) - Li, Xingang; Zheng, Chenggong; Wang, Zeli; Sui, Hong; He, Lin
Abstract: The key step for the adsorption‐desorption engineering process is the reversible in‐situ desorption of the adsorbent without VOCs (volatile organic compounds) accumulation. Our previous results show that the mesoporous silica gel performs well in adsorbing and desorbing the VOCs due to their capillary condensation in the mesopores. However, the microporous silica performs better in adsorbing though poorer in desorbing VOCs because of the direct interaction between VOCs molecules and the adsorbent wall in the micropores. Herein, the adsorption and desorption of o‐ xylene on two silica gels (SG) with different pore size distribution by vacuum swing adsorption (VSA) has been systematically studied. The equilibrium adsorption and desorption experiments of two kinds of silica gels at different loading heights in fixed bed show that the concentration front of o‐ xylene in microporous SG disperses slowly. However, the concentration front of o‐ xylene in mesoporous SG is significantly dispersed. To improve the overall efficiency of adsorption‐desorption, the mesoporous and microporous SGs are loaded together in the fixed bed. It was found that the increase in the microporous SG loading percentage facilitated the adsorption capacity but deteriorated its desorption efficiency, while the opposite occurs to the mesoporous SG. After optimization, it was observed that minimal energy consumption (1.295 kWh/m 3 VOCs gas) was used when the adsorption column is loaded with 60% SG B at the inlet and 40% of the SG A at the outlet end for o‐ xylene vapour adsorption. This finding will be useful for designing adsorbent loading in the adsorption column.